2019
DOI: 10.1101/702308
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Taxonomically informed scoring enhances confidence in natural products annotation

Abstract: 25 Mass spectrometry (MS) hyphenated to liquid chromatography (LC)-MS offers unrivalled sensitivity 26 for metabolite profiling of complex biological matrices encountered in natural products (NP) research. 27 With advanced platforms LC, MS/MS spectra are acquired in an untargeted manner on most detected 28 features. This generates massive and complex sets of spectral data that provide valuable structural 29 information on most analytes. To interpret such datasets, computational methods are mandatory. To 30 thi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 77 publications
(27 reference statements)
0
22
0
Order By: Relevance
“…The HR/MSMS datasets were organized as a molecular network (MN), which provides tandem fragmentation spectra according to their spectral similarity (Wang et al ., 2016). The experimental fragmentation dataset in the MN was annotated by comparison with a database of simulated spectra of natural products obtained by in silico MS/MS fragmentation (Allard et al ., 2016) and following a taxonomically informed metabolite annotation process (Rutz et al ., 2019). In a MN, a cluster of nodes is generally indicative of a family of structurally related molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HR/MSMS datasets were organized as a molecular network (MN), which provides tandem fragmentation spectra according to their spectral similarity (Wang et al ., 2016). The experimental fragmentation dataset in the MN was annotated by comparison with a database of simulated spectra of natural products obtained by in silico MS/MS fragmentation (Allard et al ., 2016) and following a taxonomically informed metabolite annotation process (Rutz et al ., 2019). In a MN, a cluster of nodes is generally indicative of a family of structurally related molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The converted files were treated using the MZMine software suite v. 2.39 (Pluskal et al ., 2010). The dereplication strategy consisted of a combination of molecular networking and an in silico generated fragmentation database spectral matching, informed by taxonomic information (Rutz et al ., 2019). Dereplication results were then visualized as chemical structures, and their relative abundance in both samples was estimated as previously described (Allard et al ., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, metascores tend to prefer highly cited “blockbuster metabolite” candidates; hence, evaluation results, which are carried out using mainly such “blockbuster metabolites”, are often exaggerated. Similar limitations are associated with metascores based on taxonomy 57 as again, this information is not available for “truly novel” structures. Thus, we ignored metascore methods in our evaluations.…”
Section: Methodsmentioning
confidence: 95%
“…Finally, some tools use networks for structure annotations; networks may be based on spectral similarity in the LC-MS/MS run, or structural similarity in the metabolite database [57][58][59][60] .…”
Section: In Silico Methods and Related Workmentioning
confidence: 99%
“…data and thus open exciting perspectives in the fields of dereplication and NPs annotation. We previously demonstrated that taxonomically-informed metabolite annotation critically improves the NPs annotation process (Rutz et al, 2019). The availability of an open repository linking chemical objects to both their spectral information and biological occurrences will facilitate and improve such applications.…”
Section: Conclusion and Perpectivesmentioning
confidence: 99%